A Brief Analysis of the Prognosis and Treatment of Idiopathic Membranous Nephropathy - Ji, Jingyi; Zhang, Xiaofeng (Journal of Contemporary Medical Practice, 2024)
Membranous nephropathy (MN) refers to a group of diseases characterized by the deposition of immune complexes under the epithelial cells of the glomerular basement membrane (GBM) with diffuse thickening of GBM. The prognosis of IMN is diverse, untreated, about 1/3 of patients can achieve spontaneous remission, but the course of the disease is long, it takes 15 20 months to achieve partial remission, 25 40 months to achieve complete remission, and the recurrence rate after complete remission is as high as 30%, and about 1/3 of patients will progress to end-stage renal disease (ESRD) or die of related complications within 5 15 years, and the remaining one-third of patients present with non-progressive chronic kidney disease. It is of great significance to summarize the clinical features of IMN and identify and actively intervene in the risk factors of IMN prognosis as early as possible to protect renal function. Although the etiology and pathogenesis of this disease are not clearly understood, and there is great controversy in the treatment plan, many literature studies have shown that active treatment can effectively alleviate proteinuria and improve renal survival, thereby greatly prolonging the time to reach ESRD, and greatly reducing the mental and economic pressure of patients and families.